Preservice elementary teachers' perceptions of their self-efficacy in teaching thinking skills - BAYSAL, ZELİHA NURDAN (ELSEVIER SCIENCE BV, 2010)
Preservice teachers' self-efficacy in teaching the thinking skills included in the curriculum is important to the achievement of objectives. What are the self-efficacy levels of preservice teachers in teaching thinking skills? The present study aims to determine the self-efficacy of preservice teachers in this area. The study is of a descriptive nature and uses the survey model. The study sample consists of a total of 263 third and fourth-year students from Marmara University, Ataturk Education Faculty, Elementary Teacher Education Department. The scale used in the study had been developed for Tebbs' PhD dissertation entitled Assessing Teachers' Self-Efficacy towards Teaching Thinking Skills and was adapted into Turkish by Kaya (2008). The data were analyzed by using arithmetic means, standard deviation, independent samples t- test, analysis of variance, and Pearson product-moment correlation analysis. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Thinking skills; self-efficacy; problem-solving; decision-making; creative thinking; critical thinking